prove this question
Attachments:
![](https://hi-static.z-dn.net/files/d09/2d5061e47c5eb94ca13d3ac26b7951c7.jpg)
Answers
Answered by
2
Step-by-step explanation:
secA+tanA-1/tanA-secA+1
=secA+tanA-(sec²A-tan²A)/tanA-secA+1
=(secA+tanA)(1-secA+tanA)/ tanA-secA+1
=secA+tanA
=1/cosA+sinA/cosA
=1+sinA/cosA
=(1+sinA)(1-sinA)/cosA(1-sinA)
=1-sin²A/cosA(1-sinA)
=cos²A/cosA(1-sinA)
=cosA/1-sinA
thankyou
Attachments:
![](https://hi-static.z-dn.net/files/d0d/aa20ad32d1141d1a202f11d7d9c4fe00.jpg)
Similar questions